The evaluation of JAK inhibitors on effect and safety in alopecia areata: a systematic review and meta-analysis of 2018 patients - Mao, Mei-qi; Ding, Yu-xin; Jing, Jing; Tang, Zhen-wei; Miao, Yu-jie; Yang, Xiao-shuang; Chen, Yu-hong; Chen, Sheng-zhao; Wu, Xian-jie; Lu, Zhong-fa (Frontiers in Immunology, 2023)
Background JAK inhibitors treat various autoimmune diseases, but an updated systematic review in treating alopecia areata is currently lacking. Objective Evaluate the specific efficacy and safety of JAK inhibitors in alopecia areata by systematic review and meta-analysis. Methods Eligible studies in PubMed, Embase, Web of Science, and Clinical Trials up to May 30, 2022, were searched. We enrolled in randomized controlled trials and observational studies of applying JAK inhibitors in alopecia areata. Results 6 randomized controlled trials with 1455 patients exhibited SALT50 (odd ratio [OR], 5.08; 95% confidence interval [CI], 3.49-7.38), SALT90 (OR, 7.40; 95% CI, 4.34-12.67) and change in SALT score (weighted mean difference [WSD], 5.55; 95% CI, 2.60-8.50) compared to the placebo. The proportion of 26 observational studies with 563 patients of SALT5 was 0.71(95% CI, 0.65-0.78), SALT50 was 0.54(95% CI 0.46-0.63), SALT90 was 0.33(95% CI, 0.24-0.42), and SALT score (WSD, -2.18; 95% CI, -3.12 to -1.23) compared with baseline. Any adverse effects occurred in 921 of 1508 patients; a total of 30 patients discontinued the trial owing to adverse reactions. Limitations Few randomized controlled trials met the inclusion criteria and insufficiency of eligible data. Conclusion JAK inhibitors are effective in alopecia areata, although associated with an increased risk.